Management of Diverticular Bleeding: Evaluation, Stabilization, Intervention, and Recurrence of Bleeding and Indications for Resection after Control of Bleeding - Mohammed Ilyas, Mohammed Iyoob; Szilagy, Eric J. (Clinics in Colon and Rectal Surgery, 2018)
Diverticular bleeding is the most common cause of lower gastrointestinal bleeding with nearly 200,000 admissions in the United States annually. Less than 5% of patients with diverticulosis present with diverticular bleeding and present usually as painless, intermittent, and large volume of lower gastrointestinal bleeding. Management algorithm for patients presenting with diverticular bleeding includes resuscitation followed by diagnostic evaluation. Colonoscopy is the recommended first-line investigation and helps in identifying the stigmata of recent hemorrhage and endoscopic management of the bleeding. Radionuclide scanning is the most sensitive but least accurate test due to low spatial resolution. Angiography is helpful when patients are actively bleeding and therapeutic interventions are performed with angioembolization. Surgery for diverticular bleeding is necessary when associated with hemodynamic instability and after failed endoscopic or angiographic interventions. When the bleeding site is localized preoperatively, partial colectomy is sufficient, but subtotal colectomy is necessary when localization is not possible preoperatively.
Keywords: lower gastrointestinal bleeding; diverticular bleeding; angiography; embolization